Antiplatelet Therapy in Atherothrombotic Diseases: Similarities and Differences Across Guidelines - Jourdi, Georges; Marquis-Gravel, Guillaume; Martin, Anne-Céline; Lordkipanidzé, Marie; Godier, Anne; Gaussem, Pascale (Frontiers in Pharmacology, 2022)
Antiplatelet therapy, mainly consisting of aspirin and P2Y12 receptor antagonists, is the cornerstone of the pharmacological treatment and prevention of atherothrombotic diseases. Its use, especially in secondary cardiovascular prevention, has significantly improved patient clinical outcomes in the last decades. Primary safety endpoint (i.e., bleeding complications) remain a major drawback of antiplatelet drugs. National and international societies have published and regularly updated guidelines for antiplatelet therapy aiming to provide clinicians with practical recommendations for a better handling of these drugs in various clinical settings. Many recommendations find common ground between international guidelines, but certain strategies vary across the countries, particularly with regard to the choice of molecules, dosage, and treatment duration. In this review, we detail and discuss the main antiplatelet therapy indications in the light of the different published guidelines and the significant number of recently published clinical trials and meta-analyses and highlight the areas that deserve further investigation in order to improve antiplatelet therapy in patients with atherothrombotic diseases.